Laser Powder Bed Fusion of copper alloy-based multi-materials: Manufacturing and process optimization : A Literature Review - Laurikainen, Kalle (My University, 2025)
The advancement of multi-material additive manufacturing, particularly through laser powder bed fusion, presents significant potential for additive manufacturing. New technologies could enable production of copper alloy-based parts with enhanced mechanical and thermal functionality. This literature review investigates the current state of copper alloy/metal multi-material fabrication, focusing on the challenges of interfacial bonding, material compatibility, and process optimization. Copper alloys such as CuCrZr and Cu10Sn have been identified as promising candidates for integration with an assortment of steels due to their favorable laser absorption properties compared to pure copper. Despite successful demonstrations, manufacturing challenges persist, particularly due to copper’s high reflectivity and thermal conductivity. Key strategies, such as process parameter-, post-processing and scanning strategy optimization were analyzed across various studies. Effective interfacial bonding has been achieved through a multitude of techniques such as compositional gradient transitions, strategic scan path planning (e.g., staggered island and interlayer rotation), and post-processing heat treatments such as hot isostatic pressing and age hardening. Notably, this review highlights the lack of comprehensive research on wider array of material combinations. Additionally, porosity, surface roughness, and mechanical strength varied significantly across case studies depending on processing strategies and material combinations.
Keywords: Multi-material, additive manufacturing, powder bed fusion, copper alloy, process optimization